SEIZURES WITH ANTI-SEIZURE DRUG - Brattiya R, Keerthana; K, Bhuvaneshwari (Asian Journal of Pharmaceutical and Clinical Research, 2017)
This case study is to report and explore the etiology of a case of refractory seizures due to overdosage of phenytoin tablets. A case report from the Department of Neurology generated through voluntary adverse drug reaction (ADR)reporting stated phenytoin overdosage leading to refractory status epilepticus which did not respond to any of the antiepileptic drugs. A 33-year-old female patient with the history of consumption 15 tablets of phenytoin and a metal ring as part of a suicidal bid a month ago, presented with unconsciousness, persistent seizures, and gangrene of fingers. Magnetic resonance imaging showed generalized atrophic changes of the cerebrum and cerebellum. Electroencephalogram suggested multifocal onset status epilepticus. The patient did not respond to standard emergency treatment of status epilepticus with known antiepileptic drugs and was treated with thiopentone infusion under mechanical ventilation, which controlled her seizures as long as she was maintained under the infusion. Causality analysis using the World Health Organization scale categorizes this ADR as possibleâ€, as the patient is a known case of seizure disorder with additional cerebral changes. Hence, the disease could have had an influence over the toxic reaction. To conclude, seizures are a rare complication of phenytoin. Seizures can be prevented by evaluating therapeutic plasma concentration of phenytoin. In this case, the patient was on chronic treatment, and due to intentional toxicity, she progressed to a refractory state of seizures. This could have occurred because of the unique kinetic profile of phenytoin, small therapeutic index, genetic variation in drug metabolizing enzymes, and saturated sodium channels.